Geriatric assessment and intervention in older vulnerable patients undergoing surgery for colorectal cancer: a protocol for a randomised controlled trial (GEPOC trial) - Troels G. Dolin; Marta Mikkelsen; Henrik L. Jakobsen; Tyge Nordentoft; Trine S. Pedersen; Anders Vinther; Bo Zerahn; Kirsten K. Vistisen; Charlotte Suetta; Dorte Nielsen; Julia S. Johansen; Cecilia M. Lund (BMC Geriatrics, 2021)
Abstract Background The incidence of colorectal cancer (CRC) increases with age. Older patients are a heterogeneous group ranging from fit to frail with various comorbidities. Frail older patients with CRC are at increased risk of negative outcomes and functional decline after cancer surgery compared to younger and fit older patients. Maintenance of independence after treatment is rarely investigated in clinical trials despite older patients value it as high as survival. Comprehensive geriatric assessment (CGA) is an evaluation of an older persons’ medical, psychosocial, and functional capabilities to develop an overall plan for treatment and follow-up. The beneficial effect of CGA is well documented in the fields of medicine and orthopaedic surgery, but evidence is lacking in cancer surgery. We aim to investigate the effect of CGA on physical performance in older frail patients undergoing surgery for CRC. Methods GEPOC is a single centre randomised controlled trial including older patients (≥65 years) undergoing surgical resection for primary CRC. Frail patients (≤14/17 points using the G8 screening tool) will be randomised 1:1 to geriatric intervention and exercise (n = 50) or standard of care along (n = 50) with their standard surgical procedure. Intervention includes preoperative CGA, perioperative geriatric in-ward review and postoperative follow-up. All patients in the intervention group will participate in a pre- and postoperative resistance exercise programme (twice/week, 2 + 12 weeks). Primary endpoint is change in 30-s chair stand test. Assessment of primary endpoint will be performed by physiotherapists blinded to patient allocation. Secondary endpoints: changes in health related quality of life, physical strength and capacity (handgrip strength, gait speed and 6 min walking test), patient perceived quality of recovery, complications to surgery, body composition (Dual-energy X-ray absorptiometry and bioelectric impedance), serum biomarkers, readmission, length of stay and survival. Discussion This ongoing trial will provide valuable knowledge on whether preoperative CGA and postoperative geriatric follow-up and intervention including an exercise program can counteract physical decline and improve quality of life in frail CRC patients undergoing surgery. Trial registration Prospectively registered at Clinicaltrials.gov NCT03719573 (October 2018).